2021
DOI: 10.3389/fcvm.2021.690262
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Quantitative Flow Ratio and Intravascular Imaging-defined Vulnerable Plaque Characteristics in Patients With Stable Angina and Non-ST-segment Elevation Acute Coronary Syndrome

Abstract: Background: This study aimed to examine whether quantitative flow ratio (QFR), an angiography-based computation of fractional flow reserve, was associated with intravascular imaging-defined vulnerable plaque features, such as thin cap fibroatheroma (TCFA) in patients with stable angina, and non-ST-segment elevation acute coronary syndrome.Methods: Patients undergoing optical coherence tomography (OCT) or intravascular ultrasound (IVUS) examinations were identified from two prospective studies and their interro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Kanno et al (84) found that QFR severity was associated with a higher prevalence of OCT-defined thin-cap fibroatheroma (TCFA) in stable patients. Similar findings were reported by Dan et al (85) and Zuo et al (86), showing that lower QFR value was related to IVUS or OCT-defined vulnerable plaque features (i.e., minimal lumen area, plaque burden and TCFA) in both stable angina and NSTEMI patients. However, in a recent study of 87 patients with CCS, QFR was not associated with features of plaque vulnerability such as fibrous cap thickness, although significant correlations were found between QFR and OCT-derived intraluminal stenosis parameters (87).…”
Section: Qfr and Intravascular Imaging-defined Plaque Vulnerabilitysupporting
confidence: 89%
“…Kanno et al (84) found that QFR severity was associated with a higher prevalence of OCT-defined thin-cap fibroatheroma (TCFA) in stable patients. Similar findings were reported by Dan et al (85) and Zuo et al (86), showing that lower QFR value was related to IVUS or OCT-defined vulnerable plaque features (i.e., minimal lumen area, plaque burden and TCFA) in both stable angina and NSTEMI patients. However, in a recent study of 87 patients with CCS, QFR was not associated with features of plaque vulnerability such as fibrous cap thickness, although significant correlations were found between QFR and OCT-derived intraluminal stenosis parameters (87).…”
Section: Qfr and Intravascular Imaging-defined Plaque Vulnerabilitysupporting
confidence: 89%
“…Our previous study also supported this observation, reporting that high‐risk plaque characteristics such as thin‐cap fibroatheroma, lipid‐rich plaque, and thrombus, identified by optical coherence tomography, were negatively associated with 3‐dimensional QFR. 26 After controlling for patient characteristics, our study found a marginal association between sex and FFR values. These findings imply that other factors or confounders may be responsible for the observed difference in FFR values between men and women.…”
Section: Discussionmentioning
confidence: 59%
“…The threshold was defined as FFR ≤ 0.80 to indicate functional ischemia [ 1 ]. The details of the procedure have been described in our previous reports [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%